Determining the Levels of Some Heavy Metals in Springs and Groundwater Wells in the Northeastern Region of Libya - El Awamy, Ifdial O.; Abduljalil , Ruqayah. A.; Abduljalil, Omukalthum A. (Al-Mukhtar Journal of Sciences, 2020)
This study was designed to detect heavy metals (Zn, Cd, Pb, and Cu) in several springs and groundwater wells in the northeastern region of Libya. Samples were collected from different regions in both seasons (dry and wet). An atomic absorption spectrophotometry equipped with Slotted Tube Atomic Trap (STAT) was used. The limit of detection (LOD) was in the range of 0.008 to 0.03 μg mL-1, and the limit of quantification (LOQ) was in the range of 0.02 to 0.09 μg mL-1. % RSD (relative standard deviations) ranged between 0.0001 to 0.329%. Results showed the presence of heavy metal residues in the regions in two seasons (dry-wet) during the study in some springs and groundwater wells. The zinc (Zn), cadmium (Cd), and Copper (Cu) values were below permitted limits, according to the World Health Organization (WHO), Libyan National Center for Standardization (LNCSM), and Food and Agriculture Organization (FAO). Lead (Pb) in the dry season was much higher than the wet season in accordance with WHO and LNCSM. The other values were below permissable limits according to WHO, LNCSM, and FAO. This study’s results show the presence of dangerous levels of lead during the dry season in the groundwater wells on SahlAlmarj I, Alabyar III. Overall, the investigation of chemical and agricultural fertilizers is an effective method of monitoring the quality of drinking water. Such investigations are needed to identify possible sources of contamination of storage tanks and pipelines to ensure the delivery of safe drinking water to end-users.